2013
DOI: 10.1002/mbo3.148
|View full text |Cite
|
Sign up to set email alerts
|

Disassembly of the cystovirus ϕ6 envelope by montmorillonite clay

Abstract: Prior studies of clay–virus interactions have focused on the stability and infectivity of nonenveloped viruses, yielding contradictory results. We hypothesize that the surface charge distribution of the clay and virus envelope dictates how the components react and affect aggregation, viral stability, and infectivity. The bacteriophage Cystoviridae species φ6 used in this study is a good model for enveloped pathogens. The interaction between φ6 and montmorillonite (MMT) clay (the primary component of bentonite)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…The viable virus population in the control was 3.5 × 10 11 , in good agreement with our estimates from turbidity (which includes non-infectious virions). φ6 in the montmorillonite aggregates displayed a significant decrease in infectivity for both virions in the aggregates (14% viable) and planktonic cells (35% viable), which is consistent with results from our previous work (Block et al, 2014). In the φ6-kaolinite and φ6-illite aggregates, the virions in the pellets, i.e.…”
Section: Sds-page and Virus Viabilitysupporting
confidence: 91%
See 4 more Smart Citations
“…The viable virus population in the control was 3.5 × 10 11 , in good agreement with our estimates from turbidity (which includes non-infectious virions). φ6 in the montmorillonite aggregates displayed a significant decrease in infectivity for both virions in the aggregates (14% viable) and planktonic cells (35% viable), which is consistent with results from our previous work (Block et al, 2014). In the φ6-kaolinite and φ6-illite aggregates, the virions in the pellets, i.e.…”
Section: Sds-page and Virus Viabilitysupporting
confidence: 91%
“…Prior work (Block et al, 2014) has demonstrated that φ6 does not aggregate in buffer A at neutral pH, therefore K vv = 0 (Eq. (6)).…”
Section: Isolated φ6 and Sediment Turbiditymentioning
confidence: 99%
See 3 more Smart Citations